Status of Amphibian Studies and Conservation in Bhutan - Das, Indraneil; Wangyal, Jigme Tshelthrim (Natural History Publications (Borneo) Sdn. Bhd, 2014)
The Himalayan Kingdom of Bhutan, referred to as ‘Drukyul’, or the Land of the Thunder Dragon, by the Bhutanese is a small (area: 38,394 km2 , or slightly larger than Switzerland) landlocked nation, situated between China (Tibet) and India, straddling the southern slopes of the eastern Himalayas. The Kingdom has an eastwest extent of about 300 km and a north-south extent of 170 km, and comprises mostly evergreen forest-clad mountains. The country has a long (470 km) border with Tibet (China’s Xizang Autonomous Region) to the north and northwest and a longer combined one (605 km) with the Indian state of Sikkim to the west, Poschim Banga (formerly, West Bengal) to the southwest, Assam to the south and southeast, and Arunachal Pradesh to the east. Sikkim, a tiny state of the Indian union separates Bhutan from Nepal, while Poschim Banga separates it from Bangladesh. The traditional border with Tibet follows the Chumbi valley watershed in the northwest and the crest of the Himalayas in the north while the border with India in the south is dictated by a treaty with British India in the Nineteenth Century; that frontier essentially follows the contours made by the Himalayan foothills with the plains. The border with Tibet is traditional, following the watershed of the Chumbi Valley in the northwest and the crest of the Himalayas in the north. Estimates of forest cover in the Kingdom vary from about 81% (Anonymous 2011), to 55% (Meyfroidt and Lambin 2010). According to the latter source, closed or partially closed forests account for 22% of Bhutan, and about seven percent is under permanent snow and glaciers. About three percent is cultivated or consists of agricultural land, while another four percent is counted as meadows and pastures. The rest of the land is either barren, rocky, or scrubland (Anonymous 2012).